How far will they go? Distance and driving times that north American men travel to see a reproductive urologist. (24th August 2022) - Chen, Jian; Jarvi, Keith; Lajkosz, Katherine; Smith, James; Lau, Susan; Lo, Kirk; Grober, Ethan; Samplaski, Mary K.
Abstract: Male factor infertility affects about 50% of infertile couples. However, male factor infertility is largely under‐evaluated due to multiple reasons. This study is to determine the time men travel for fertility evaluation, and factors associated with driving longer. Data from the Andrology Research Consortium were analysed. Driving distance and time were calculated by comparing "patient postal code" with "clinic postal code", then stratified into quartiles. Patients with the longest driving times (> 75th percentile [Q4]) were compared with those having shorter driving times. Logistic regression analysis was used to identify factors associated with longer driving times. Sixteen clinics and 3029 men were included. The median driving distance was 18.1 miles, median driving time was 32 min, and Q4 driving time was 49 min. Factors correlated with having Q4 driving time were age > 30 years, native Indian and Caucasian race, body mass index (BMI) > 30 kg/m 2, history of miscarriage, children with previous partner, self‐referral, prior vasectomy, and prior marijuana use. On logistic regression, males aged < 30 years were more likely to be in Q4 for driving time versus older males. Blacks and Asians were less likely to travel further than Caucasians. Overweight/obese men, those having children with previous partner, and with prior vasectomy were more likely to be in Q4 travelling time. Factors correlated with longer driving times include younger age, native Indian and Caucasian race, higher BMI, children with prior partner, and prior vasectomy. These may reflect groups that drive long distances for reproductive care. The study provides an opportunity to better access these groups and minimise their barriers to fertility care.